108k views
2 votes
Is this answer right?

Is this answer right?-example-1
User Blklight
by
5.1k points

2 Answers

5 votes

Answer:

0

Explanation:


(15 - 6)^(2) / 3 - {3}^(3) = {9}^(2) / 3 - 27 = 81 / 3 - 27 = \\ \\ 27 - 27 = 0

According to the Order of Operations [GEMS\BOMDAS\PEMDAS etc.], evaluate everything in grouping symbols first, then exponents [indices, roots, etcetera], Division & Multiplication from left to right, then Subtraction & Addition from right to left [or left to right as you know what you are doing correctly].

I am joyous to assist you anytime.

User Bajran
by
5.0k points
6 votes

Solve using the rules of PEMDAS (Parentheses, Exponent, Multiplication, Division, Addition, Subtraction)

REMEMBER: IF NOT APPLICABLE TO THE EQUATION YOU MAY SKIP THAT STEP IN PEMDAS .

3(8 - 2) + 4 = 22

Parentheses...

(15 - 6)² ÷ 3 - 3³

15 - 6 = 9

(9)² ÷ 3 - 3³

Exponent....

9² ÷ 3 - 3³

In this case you have two exponents. Always apply the steps from left to right

÷ 3 - 3³

9² = 81

81 ÷ 3 -

3³ = 27

81 ÷ 3 - 27

Division...

81 ÷ 3 - 27

81 ÷ 3 = 27

27 - 27

Subtraction...

27 - 27 = 0

0

Your mistake:

You subtracted 3 - 27 before dividing 81 by 3. Remember that according to the rules of PEMDAS division must come before subtraction

Hope this helped!

~Just a girl in love with Shawn Mendes

User Abonet
by
5.3k points